2020
DOI: 10.1186/s12885-020-06926-x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risks in Lynch syndrome, Lynch-like syndrome, and familial colorectal cancer type X: a prospective cohort study

Abstract: Background: Individuals with pathogenic germline variants in DNA mismatch repair (MMR) genes are at increased risk of developing colorectal, endometrial and other cancers (Lynch syndrome, LS). While previous studies have extensively described cancer risks in LS, cancer risks in individuals from families without detectable MMR gene defects despite MMR deficiency (Lynch-like syndrome, LLS), and in individuals from families fulfilling the Amsterdam-II criteria without any signs of MMR deficiency (familial colorec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 37 publications
(72 reference statements)
2
56
0
2
Order By: Relevance
“…MSI/dMMR gastric carcinomas tend to occur as poorly differentiated adenocarcinomas in the antrum of elderly patients and to display abundant T-cell infiltration, intestinal histological type, a lack of lymph node metastases, and TNM (Tumor Node Metastasis) stage I-II [ 75 , 76 ]. In LS, the cumulative risk of developing gastric cancer is estimated to be 2.5–6% [ 2 , 4 ]. LS-associated gastric cancers are mostly of the intestinal type, but the diffuse type is also observed [ 77 ].…”
Section: Tumor Characteristics In Lynch Syndromementioning
confidence: 99%
See 3 more Smart Citations
“…MSI/dMMR gastric carcinomas tend to occur as poorly differentiated adenocarcinomas in the antrum of elderly patients and to display abundant T-cell infiltration, intestinal histological type, a lack of lymph node metastases, and TNM (Tumor Node Metastasis) stage I-II [ 75 , 76 ]. In LS, the cumulative risk of developing gastric cancer is estimated to be 2.5–6% [ 2 , 4 ]. LS-associated gastric cancers are mostly of the intestinal type, but the diffuse type is also observed [ 77 ].…”
Section: Tumor Characteristics In Lynch Syndromementioning
confidence: 99%
“…More than 60% of MSI/dMMR small bowel adenocarcinomas may be LS-related according to the family history and MMR protein expression pattern [ 81 ]. The lifetime risk for LS patients to develop small bowel cancer is estimated to be 4–12% [ 2 , 4 , 82 ]. LS-associated tumors are mainly located in the duodenum (43%) and the jejunum (33%), only 7% being located in the ileum [ 82 ].…”
Section: Tumor Characteristics In Lynch Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…Pathogenic germline variants in MMR genes, causative for LS, were first discovered in the 1990s, with MSH2 being first (1993), followed by MLH1 (1994) and PMS2 (1994), MSH6 (1997) , and EpCAM (2009) [ 2 , 3 , 4 , 5 , 6 ]. Besides an increased risk of up to 57.1% to develop colorectal cancer (CRC), female carriers are also at high risk to develop gynecological malignancies, such as endometrial cancer (EC) and cancer in the ovaries (OC) [ 7 , 8 , 9 ]. A recent study showed that the risks for EC development by age 75 are 37%, 48%, 41%, and 12% for MLH1 , MSH2 , MSH6, and PMS2 carriers, respectively.…”
Section: Introductionmentioning
confidence: 99%